Questionnaire Survey on Behavior for Natural Ventilation and Electricity Consumption in Terraced Houses: A case study of Johor Bahru City - Tetsu, Kubota; Ahmad, Supian (2005)
This paper presents the findings of a questionnaire survey on behavior for natural ventilation and electricity consumption among selected households in Johor Bahru City. The main purpose of this survey was to examine effects of natural ventilation on energy saving among households. The survey revealed that the reduction of both numbers and use of air-conditioners were the most effective means for electricity saving among households. Although approximately 80% of respondents opened their windows during the daytime, only arounds 10% did so during the nighttime. It is very important to encourage occupants to open windows especially during the nighttime for achieving energy saving objectives.